Evidence for a biological control-induced regime shift between floating and submerged invasive plant dominance in South Africa - Strange, Emily Frances (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
South Africa has a long history battling the establishment and spread of invasive floating macrophytes. The negative consequences of these are costly both economically and ecologically. They form dense mats on the water's surface that deplete resources such as light and oxygen to the submerged community, which creates anoxic conditions, reduces biodiversity and limits access to freshwater. The past thirty years of South African invasive plant research and the implementation of nationwide biological control programmes has led to widespread control of these species in many degraded systems. Such initiatives are aimed at restoring access to potable freshwater and increasing native biodiversity. However, in recent years, where there has been a decline in floating invasive plant populations, an increase in the establishment and spread of submerged invasive plant species has been observed. Species such as Brazilian waterweed (Egeria densa (Planch.) (Hydrocharitaceae)) and Eurasian watermilfoil (Myriophyllum spicatum (L.) (Haloragaceae)) have been recorded in South African freshwater systems, posing significant threats to aquatic ecosystems. This thesis proposes that the biological control of floating invasive plants, which occurs in numerous dams and rivers nationwide, is the catalyst of a regime shift from floating invasive to submerged invasive plant dominance. Regime shifts are large and often sudden changes in the key structure and functioning of ecosystems, and studies into their occurrence and driving mechanisms broadens understanding of community structures and can guide effective resource management. In order to explore the existence of this new regime shift, a multi-platform approach using controlled experiments and ecological modelling techniques was employed. A model system was created consisting of a floating invasive (Pistia stratiotes L. (Araceae)), a submerged invasive (E. densa) and an ecologically analogous submerged native plant species (Lagarosiphon major (Ridl.) Moss (Hydrocharitaceae)). A suite of experiments was conducted to explore the interactions between the floating and submerged plants under varying regimes of floating plant biological control and levels of nutrient loading. These experiments revealed a competitive advantage of the invasive E. densa over the native L. major that increased by 86% under heavy nutrient loading. The relative growth rate and accumulated biomass of E. densa was significantly higher for plants grown in the presence of biologically controlled P. stratiotes (compared to insect free plants). This demonstrates a high capacity for the invasive E. densa to capitalise on resources made newly available through the biological control of the floating plants. In contrast, the native L. major fared poorly when grown in the presence of the floating P. stratiotes, regardless of applied biological control measures. The experimental observations were then used to parameterise a mathematical model, built to provide a holistic understanding of the individually assessed interactions which work together as the driving mechanisms underpinning the newly identified regime shift. This thesis utilised a multi-platform approach to build the first body of evidence in support of a newly recognised regime shift between floating invasive and submerged invasive plant dominance, as driven by biological control. The results indicate that a reduction in the nutrient loading of South Africa's freshwater systems will reduce negative impacts of submerged invasive macrophytes, whilst increasing system resilience against future invasion. The evidence presented has the potential to better inform management of South Africa's freshwater systems and highlights the importance of integrating multi-trophic interactions when considering future invasive plant management. This research also opens up a multitude of possibilities for studies into submerged plant invasion mechanisms and resilience of native macrophyte communities in South Africa, and further afield.
Keywords: Uncatalogued